Mesoporous NiCo2O4 nanoneedles grown on 3D graphene-nickel foam for supercapacitor and methanol electro-oxidation. (1st January 2015) - Yu, Mei; Chen, Jianpeng; Liu, Jianhua; Li, Songmei; Ma, Yuxiao; Zhang, Jingdan; An, Junwei
Abstract: Mesoporous NiCo2 O4 nanoneedles were directly grown on three dimensional (3D) graphene-nickel foam which was prepared by chemical vapor deposition, labeled as NCO/GNF. The structure and morphology of NCO/GNF were investigated by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, element mapping and Raman spectroscopy. The NCO/GNF was employed as electrodes for supercapacitor and methanol electro-oxidation. When used for supercapacitor, the NiCo2 O4 nanoneedles exhibit hi exhibit high specific capacitance (1588 F g −1 at 1 A g −1 ), high power density and energy density (33.88 Wh kg −1 at 5 kW kg −1 ) as well as long cycling stability. In methanol electro-oxidation, the NiCo2 O4 nanoneedles deliver high electro-oxidation activity (93.3 A g −1 at 0.65 V) and electro-oxidation stability. The good electrochemical performance of NiCo2 O4 nanoneedles is attributed to the 3D structure with large specific area, high conductivity and fast ions/electrons transport.